Environmental Concerns Motivate Intention to Utilize Free Bus Services:An Empirical Study in Malaysia - Jayaraman, K.; Ng, Chee Hin; Stocker, Klaus; Kiumarsi, S. (Indian Journal of Marketing, 2016)
The free bus concept is one of the strategies used in many countries to reduce the traffic congestion problems. In Australia, free buses have been introduced in selected places to protect the nature of the city, but not for office commuters. Malaysia is unique in the sense that the free bus service is funded by the government as an alternative for commuting to ease the traffic woes. The purpose of this study was to identify the factors influencing the utilization of the free bus service since the free bus service is underutilized by 55% even after 2 years of its implementation in Malaysia. This study examined the relationship between five independent variables (predictors) namely, perceived ease of use (PE), perceived usefulness (PU), moral obligations (MO), subjective norm (SN), and financial incentives (FIN) on the intention to utilize the free bus service. From the current empirical study of 142 respondents, 60.6% were utilizing the free bus service, and 39.4% were non-users. The results showed that PE, PU, MO, and SN significantly influenced the intention to use the free bus service. It is worthwhile to mention that FIN did not statistically influence the intention to use the free bus service. It clearly indicates that people will not take it for granted anything that is given free of cost. The findings strengthen the application of the decomposed theory of planned behavior (DTPB) in predicting Malaysian commuters’ behavior. The research findings also indicate that people have started taking note of the environmental problems and the ultimate benefits of using public transport for primary travel to resolve traffic congestion issues.